Was Feyerabend a Popperian? Methodological issues in the History of the Philosophy of Science. (June 2016) - Collodel, Matteo
Abstract: For more than three decades, there has been significant debate about the relation between Feyerabend and Popper. The discussion has been nurtured and complicated by the rift that opened up between the two and by the later Feyerabend's controversial portrayal of his earlier self. The first part of the paper provides an overview of the accounts of the relation that have been proposed over the years, disentangles the problems they deal with, and analyses the evidence supporting their conclusions as well as the methodological approaches used to process that evidence. Rather than advancing a further speculative account of the relation based on Feyerabend's philosophical work or autobiographical recollections, the second part of the paper strives to clarify the problems at issue by making use of a wider range of evidence. It outlines a historical reconstruction of the social context within which Feyerabend's intellectual trajectory developed, putting a special emphasis on the interplay between the perceived intellectual identity of Feyerabend, Feyerabend's own intellectual self-concept, and the peculiar features of the evolving Popperian research group. Highlights: Provides an overview of the debate over the relation between Feyerabend and Popper and disentangles the problems at issue. Proposes a contextualist approach to these problems based on socio-psychological theories and a broad evidential basis. Presents a historical account of Feyerabend's intellectual trajectory in connection with the evolving Popperian School.